Comparison of the Virulence of Pathogenic Newcastle Disease Viruses Belonging to the Same or Different Genotypes - Merino, Ruben; Villegas, Hilda; Quintana, Jose A.; Calderon, Norma (International Journal of Poultry Science, 2011)
Virulent Newcastle disease has threatened the Mexican poultry industry since 1946. Two Mexican virulent strains belonging to the Chimalhuacan (Quail2006) and Torreon (Chicken2000) lineages of genetic group V, as well as the ancient Mexican strain named Queretaro and a Beaudette C-like US strain (genotype II) were tested by pathogenesis analysis in commercial 5 weeks old broiler chickens, comparing the lesions severity on primary and secondary lymphoid organs after 24, 36, 48, 60, 72, 84 and 96 h postinoculation (hpi). Organ samples were analyzed by light and electron microscope and by virus isolation. The Quail2006 isolate caused more severe clinical signs and microscopic lesions (p